The Unknown Of İlkhanli Astronomy: The Issue Of Shams al-Dîn al-Wâbkanawî And Sultan Uljaytu Khan (Sultaniyye) Observatory - Kaya, Seyfettin (Fırat University, 2020)
One of the important scientists working in the Merâga and Tabriz observatories during the Ilkhanians Period is also Shams al-Dîn al-Wâbkanawî al-Bukharî. Shams al-Dîn al-Wâbkanawî al-Bukharî, who conducted astronomy and observation studies for 40 years since 1272, is the owner of Zij-i al-Muhaqqaq al-Sultanî, which he started writing in Sultân Uljaytu Khan Era. However, despite the beginning of the writing of this Zîj Olcaytu Han Period (1304-1316), upon his death, he was dedicated to his son, Ilhanli ruler Ebu Sa’id Bahadır (1317-1335). The most important characteristic of Zij-i al-Muhaqqaq al-Sultanî is; Zijs, which was written before, but was lost in time, is mentioned in this work, and Zij-i İlkhanî, who was alleged to have had some mistakes in it and who wrote it on the basis of previous Zijs, is criticizing and giving the original observations to justify these criticisms. Shams al-Dîn al-Wâbkanawî al-Bukharî is another development which makes important in the history of astronomy, 30 January 1283, the "the annular eclipse" is to give information about. İn addition, outside the establishment of observatories in Maragha in the Hulagu Khan Period (1256-1265) and in Tabriz in the Ghazan Khan Period (1295-1304). It is even estimated that Shams al-Dîn al-Wâbkanawî al-Bukharî worked in this observatory, which was allegedly founded in Sultaniyye during the Sultan Uljaytu Khan period (1304-1316).

İlhanlılar Dönemi’nde Merâga ve Tebrîz gözlemevlerinde çalışan önemli bilim insanlarından biri de Şemseddîn el-Vâbkanavî el-Buharî’dir. 1272 yılından beri 40 yıl boyunca astronomi ve gözlem çalışmaları yürüten Şemseddîn el-Vâbkanavî el-Buharî, Olcaytu Han Dönemi’nde yazımına başladığı Zîc-i el Muhakkak el-Sultanî adlı eserin de sahibidir. Ancak bu zîc, Olcaytu Han Dönemi’nde (1304-1316) yazılmaya başlanmasına rağmen onun ölümü üzerine oğlu İlhanlı hükümdarı Ebu Sa’id Bahadır’a (1317-1335) ithaf edilmiştir. Zîc-i el-Muhakkak el-Sultanî’nin en önemli özelliği; daha önce yazılmış, ancak zamanla kaybolmuş olan zîc adlarının bu eserde zikredilmesi ve daha önceki zîc’lere dayanılarak yazılan ve bundan dolayı içinde birtakım yanlışlıklar bulundurduğu iddia edilen Zîc-i İlhanî’yi eleştirmesi ve bu eleştirileri haklı çıkaracak özgün rasad bilgileri vermesidir. Şemseddîn el-Vâbkanavî el-Buharî’yi astronomi tarihinde önemli kılan bir diğer gelişme ise 30 Ocak 1283 yılında yapmış olduğu “halkalı güneş tutulması” hakkında bilgiler vermesidir. Ayrıca Hülağü Han Dönemi’nde 1256-1265) Merâga’da ve Gazan Han Dönemi’nde (1295-1304) Tebrîz’de gözlemevleri kurulmasının dışında Sultan Olcaytu Han Dönemi’nde de Sultaniyye’de bir gözlemevinin kurulduğu iddiası bulunmaktadır. Hatta Şemseddîn el-Vâbkanavî el-Buharî’nin, Sultan Olcaytu Han Dönemi’nde (1304-1316) Sultaniyye’de kurulduğu iddia edilen bu gözlemevinde de çalıştığı tahmin edilmektedir.
İLHANLI ASTRONOMİSİNİN BİLİNMEYENLERİ: ŞEMSEDDÎN EL-VÂBKANAVÎ VE SULTAN OLCAYTU HAN (SULTANİYYE) GÖZLEMEVİ MESELESİ